MINAT MASYARAKAT DALAM MEMASUKKAN ANAKNYA KE MDTA IRSYADUL ISLAMIYAH DESA PEMATANG SELENG KAB. LABUHAN BATU - Taufiq Hidayah; Mahariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research discusses the factors that influence people's interest in enrolling their children in MDTA Irsyadul Islamiyah and the solutions offered to increase this interest. This research uses a qualitative method with a case study approach. The techniques used in data collection are observation, interviews and documentation. The data in this study were analyzed using the Miles and Huberman technique, namely by reducing data, displaying data, and drawing conclusions. The results show that the factors driving community interest include close proximity, the experience of parents who have attended the MDTA, invitations from relatives, good reputation of teachers, adequate facilities, and affordable tuition payment system. In contrast, the lack of interest is caused by alternative options such as afternoon tutoring, lack of encouragement from parents, the desire to teach religion themselves at home, limited facilities and infrastructure, and financial constraints. This study concludes that although MDTA Irsyadul Islamiyah has various supporting factors, there are still some obstacles that cause a lack of community interest. Therefore, the MDTA tries to increase its attractiveness by improving facilities and infrastructure, implementing a more flexible tuition payment system, waiving fees for orphans, and organizing additional activities such as recitation and tahfiz qur'an, nasyid, and sports. These steps are expected to increase community interest and expand the reach of MDTAs in the neighborhood.